In silico drug discovery of melatonin receptor ligands with therapeutic potential. (3rd April 2022) - Elisi, Gian Marco; Scalvini, Laura; Lodola, Alessio; Bedini, Annalida; Spadoni, Gilberto; Rivara, Silvia
ABSTRACT: Introduction: The neurohormone melatonin ( N -acetyl-5-methoxytryptamine) regulates circadian rhythms exerting a variety of effects in the central nervous system and in periphery. These activities are mainly mediated by activation of MT1 and MT2 GPCRs. MT1 /MT2 agonist compounds are used clinically for insomnia, depression, and circadian rhythm disturbances. Area covered: The following review describes the design strategies that have led to the identification of melatonin receptor ligands, guided by in silico approaches and molecular modeling. Initial ligand-based design, mainly relying on pharmacophore modeling and 3D-QSAR, has been flanked by structure-based virtual screening, given the recent availability of MT1 and MT2 crystal structures. Receptor ligands with different activity profiles, agonist/antagonist and subtype-selective compounds, are available. Expert opinion: An insight on the pharmacological characterization and therapeutic perspectives for relevant ligands is provided. In silico drug discovery has been instrumental in the design of novel ligands targeting melatonin receptors. Ligand-based approaches has led to the construction of a solid framework defining structure-activity relationships to obtain compounds with a tailored pharmacological profile. Structure-based techniques could integrate previous knowledge and provide compounds with novel chemotypes and pharmacological activity as drug candidates for disease conditions in which melatonin receptor ligands are currently being investigated, including cancer and pain.